2005
DOI: 10.1111/j.1472-4669.2005.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemistry of microbial mats under Precambrian environmental conditions: a modelling study

Abstract: Microbial mats have arguably been the most important ecosystem on Earth over its 3.5 Gyr inhabitation. Mats have persisted as consortia for billions of years and occupy some of Earth's most hostile environments. With rare exceptions (e.g. microbial mats developed on geothermal springs at Yellowstone National Park, USA), today's mats do not exist under conditions analogous to Precambrian habitats with substantially lower oxygen and sulphate concentrations. This study uses a numerical model of a microbial mat to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 76 publications
(182 reference statements)
1
33
0
Order By: Relevance
“…Even if the total flux were far below the lower limit considered by Zahnle et al (22), dissolved O 2 concentrations in higher-productivity hot spots ("oxygen oases"), would likely have been high enough to allow steroids to be made. Such hot spots probably included phototrophic microbial mats, which could have had daytime O 2 concentrations as high as 450-650 μM within the mat layers (46). The presence of microaerobic regions of the euphotic ocean by the late Archean, and their persistence over long periods of time, is consistent with geologic and geochemical evidence for an anoxic atmosphere at that time.…”
Section: Resultssupporting
confidence: 56%
“…Even if the total flux were far below the lower limit considered by Zahnle et al (22), dissolved O 2 concentrations in higher-productivity hot spots ("oxygen oases"), would likely have been high enough to allow steroids to be made. Such hot spots probably included phototrophic microbial mats, which could have had daytime O 2 concentrations as high as 450-650 μM within the mat layers (46). The presence of microaerobic regions of the euphotic ocean by the late Archean, and their persistence over long periods of time, is consistent with geologic and geochemical evidence for an anoxic atmosphere at that time.…”
Section: Resultssupporting
confidence: 56%
“…So additional proxies must be sought. Fossilized microbial mats might hold the clue to the early origin of oxygen photosynthesis if it can be demonstrated that the expected strong redox gradients 18 existed and produced isotopic or compositional variations that can be recovered from Archaean rocks.…”
Section: From When To Whymentioning
confidence: 99%
“…In other words, as today, there is no reason to assume that the gas concentrations at weathering interfaces are directly reflective of atmospheric conditions. Indeed, 1D modeling with oxygen and sulfate boundary conditions encompassing those hypothesized from the Archean to present indicates that oxygen production and redox zonation within ancient microbial mats should have been independent of the chemistry of their environment (45). It is important to note that the attendant effects of BSCs and FMMs in the Archean would have been multiple, and would also have included enhanced mineral dissolution of underlying sediments (46) and increased flux of dissolved organic carbon to overlying waters, which in turn, facilitates transport of normally insoluble metals (e.g., Fe, Al) downstream (47).…”
Section: Significancementioning
confidence: 99%